High-thermal-conductivity graphene copper composite material and preparation method thereof

CN122588394BActive Publication Date: 2026-10-09LION OCEAN METAMATERIALS (GUANGZHOU) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611055818.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-16
Publication Date
2026-10-09
Estimated Expiration
2046-07-16

AI Technical Summary

Technical Problem

[0004]想要进一步提高该导热系数,存在较大的难度

Benefits of technology

[0018]在上述的制备方法中,所述步骤5的热压烧结的温度为800~1000℃,压力为25~35MPa,时间为0.5~1.5h;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122588394B_ABST
    Figure CN122588394B_ABST
Patent Text Reader

Abstract

The application belongs to the field of new materials, and discloses a high-thermal-conductivity graphene copper composite material and a preparation method thereof, which comprises the following steps: step 1: removing the surface oxidation layer of copper powder with a dendritic structure; step 2: dispersing organic small molecules and borides into a good solvent of the organic small molecules, and mixing the copper powder obtained in step 1, to obtain solid particles by separation; step 3: drying the solid particles in step 2; step 4: reducing the dried solid particles; and step 5: performing hot-pressing sintering and forming treatment on the product obtained in step 4. The copper powder is modified by using organic small molecules and borides, so that the thermal conductivity of the copper can be significantly improved, and the thermal conductivity coefficient of the copper can be further improved to more than 560 W / m·K.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of new materials, and in particular to a high thermal conductivity graphene-copper composite material and its preparation method. Background Technology

[0002] Coating copper particles with a carbon layer can improve certain properties of the copper particles or endow them with some new properties, such as: The publication number is CN121797964A, and the subject is a polysaccharide-coated-hydrogen pre-sintered graphene copper composite material and its preparation method. The polysaccharide-coated copper powder is prepared by polysaccharide solution (non-gelling) blending method, which is used to improve the electrical conductivity, thermal conductivity and mechanical reinforcement of copper powder.

[0003] Based on this scheme, a further patent application with publication number CN122231272A was filed, which is entitled to a composite copper powder and its preparation method, copper material and application; the patent application further improves the thermal conductivity to about 500~550W / m·K.

[0004] Further increasing this thermal conductivity presents significant challenges. Summary of the Invention

[0005] The purpose of this invention is to provide a high thermal conductivity graphene-copper composite material and its preparation method. This invention uses organic small molecules and borides to modify copper powder, which can significantly improve the thermal conductivity of copper, and its thermal conductivity can be further increased to more than 560 W / m·K. At the same time, it can also effectively improve the low coefficient of thermal expansion.

[0006] To achieve the above objectives, this application discloses: A method for preparing a high thermal conductivity graphene-copper composite material includes the following steps: Step 1: Remove the surface oxide layer from copper powder with a dendritic structure; Step 2: Disperse the small organic molecules and borides in a good solvent for the small organic molecules, and mix them with the copper powder obtained in Step 1 to separate solid particles; Step 3: Dry the solid particles from Step 2; Step 4: Reduce the dried solid particles; Step 5: Perform hot pressing sintering and molding treatment on the product obtained in Step 4; The weight of the organic small molecule is equivalent to 0.01~0.5% of the weight of the copper powder, and the weight of the boride is equivalent to 0.1~1% of the weight of the copper powder; preferably, the weight of the organic small molecule is equivalent to 0.05~0.5% of the weight of the copper powder, and the weight of the boride is equivalent to 0.5~1% of the weight of the copper powder. The organic small molecule has a molecular weight of 150-400 and contains one or more functional groups, such as carboxyl and amino groups, but does not contain monosaccharide structural units.

[0007] Patent applications CN121797964A and CN122231272A (as in Examples 2 and 4, where the thermal conductivity is reduced to 502~524 W / m·K when the polysaccharide content is relatively low) use polysaccharides as graphene precursors. In our research on polysaccharides, we have found that their improvement on thermal conductivity has reached its limit. Against this backdrop, it is an unavoidable research direction to investigate whether reducing the amount of organic matter can further improve thermal conductivity. However, previous studies have shown that less or even less organic matter than the above-mentioned schemes has an extremely weak effect on thermal conductivity. One of the features of this invention is that it uses less or fewer organic materials for coating, while simultaneously using borides for coating. The present invention selects small organic molecules as organic materials, which has the following advantages: compared with polysaccharides, the small organic molecules described in the present invention have a lower oxygen content. In the subsequent degassing sintering process, they can complete carbonization in a shorter time in the subsequent sintering process, resulting in a graphene layer with a low defect rate, which can significantly improve the interfacial thermal resistance and interfacial electrical resistance. The improvement of interfacial thermal resistance will lead to further improvement in thermal conductivity and low coefficient of thermal expansion.

[0008] Furthermore, this invention selects borides as highly efficient activators and nucleating agents. On the one hand, they can further reduce trace amounts of oxygen and clean the surface of copper powder; on the other hand, they can serve as nucleation sites for graphene growth, promoting the formation of uniform, high-quality graphene. Furthermore, we hypothesize that boron doping with small organic carbon molecules can generate micron-sized tooth-like structures such as boron carbide (B4C). This structure provides a dual function of "metallurgical bonding" and "mechanical interlocking" at the interface, greatly enhancing the interfacial bonding strength. The strongly bonded interface reduces phonon scattering at the interface. When boron atoms are present in interstitial positions or lattice sites of the copper lattice, they will cause significant lattice distortion to the surrounding copper atoms. The interfacial structure can improve the interfacial phonon transport efficiency, thereby improving thermal conductivity.

[0009] This invention achieves uniform coating of organic carbon source through wet chemical method, and then realizes in-situ growth of graphene and reduction sintering of copper powder through reduction reforming in reducing atmosphere, ultimately achieving product development with a thermal conductivity of over 560 W / m·K.

[0010] In the above preparation method, the organic small molecule is one or more combinations of oleic acid, citric acid, stearic acid, lauric acid, hexadecylamine, and octadecylamine.

[0011] Preferably, the organic small molecule is oleic acid or a combination of oleic acid and citric acid; wherein the weight percentage of oleic acid is 75wt%~100wt%.

[0012] In the above preparation method, the boride is one or more combinations of boron carbide, molybdenum boride, zirconium boride, nickel boride, lanthanum boride, calcium boride, and yttrium boride.

[0013] The copper powder has a D50 particle size of 10~35μm; the boride has a D50 particle size of 50~200nm; In the above preparation method, in step 1, the method for removing the surface oxide layer of copper powder is: reduction by reducing gas or reduction by hydrazine hydrate.

[0014] In the above preparation method, step 1 specifically involves adding copper powder to water, then adding ammonia and hydrazine hydrate for reduction; the product obtained in step 1 is an aqueous solution containing dispersed copper powder.

[0015] In the above preparation method, the good solvent in step 2 is anhydrous ethanol; the weight of the good solvent is equivalent to 0.5 to 1.5 times the weight of the copper powder.

[0016] In the above preparation method, the mixing time in step 2 is 1-2 hours; the solid particles separated in step 2 are washed with anhydrous ethanol.

[0017] In the above preparation method, the drying method in step 3 is one of rotary drying, spray drying, or fluidized bed drying; The reduction method in step 4 is as follows: the reduction operation is carried out in a reducing atmosphere containing hydrogen, and the reduction temperature is 550~650℃.

[0018] In the above preparation method, the hot pressing sintering temperature in step 5 is 800~1000℃, the pressure is 25~35MPa, and the time is 0.5~1.5h; The molding operation in step 5 is as follows: the copper ingot obtained by hot pressing and sintering is heated to 700~1000℃ and hot extruded to obtain a composite material of the preset specifications.

[0019] In addition, the present invention also provides a composite material prepared by any of the methods described above.

[0020] One of the above-described technical solutions of the present invention has at least one of the following advantages or beneficial effects: 1. The product of this invention has excellent thermal conductivity, improving the thermal conductivity of the original technical solution to over 560W / m·K; 2. The product of this invention has a good low coefficient of thermal expansion. Attached Figure Description

[0021] Figure 1 This is an EDS element distribution diagram of Example 1; Figure 2 This is a distribution diagram of element B in Example 1; Figure 3 This is a distribution diagram of element C in Example 1; Figure 4 This is a distribution diagram of element O in Example 1; Figure 5 This is a Cu elemental distribution diagram for Example 1; Figure 6 This is a La element distribution diagram for Example 1; Figure 7 This is a metallographic image of Embodiment 1 of the present invention. Detailed Implementation

[0022] The present invention will now be clearly and completely described in conjunction with embodiments thereof. It should be noted that, unless otherwise specified in the embodiments, conditions are performed under conventional conditions or conditions recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products. Unless otherwise specified, all parts used in the embodiments of the present invention are parts by weight.

[0023] Example 1 Raw material: 1 kg of dendritic electrolytic copper powder (purity ≥ 99.8%, average particle size: 30 μm).

[0024] Step 1: Remove oxide film: Add 1 kg of copper powder to 5 L of high-purity water, disperse by mechanical stirring, add 50 mL of ammonia and 20 mL of hydrazine hydrate, stir at room temperature for 30 minutes to obtain copper powder dispersion.

[0025] Step 2: Oleic acid coating: Disperse 3g oleic acid, 0.5g citric acid, and 5g lanthanum boride with an average particle size of 100nm (i.e., 0.3% oleic acid, 0.05% citric acid, and 0.5% lanthanum boride) in 1L anhydrous ethanol. Add this mixture to the above copper powder dispersion and continue stirring for 1.5 hours. Then centrifuge to settle, discard the supernatant, and wash repeatedly with anhydrous ethanol three times.

[0026] Step 3: Rotary evaporation drying: Transfer the material to a rotary evaporator, water bath at 65℃, vacuum degree -0.085MPa, and dry until the material is in a loose powder state.

[0027] Step 4: Hydrogen reduction and reforming: Place the dry powder into a tube furnace, introduce a mixture of hydrogen and argon in a ratio of 3:7 (volume ratio), heat to 600°C at 8°C / min, hold for 2 hours, then cool to room temperature with the furnace and remove under a nitrogen atmosphere.

[0028] Step 5: Hot pressing and extrusion: The treated copper powder is placed in a graphite mold and sintered in a vacuum hot press furnace at a temperature of 850℃ and a pressure of 30MPa for 1 hour to obtain copper ingots. The copper ingots are then heated to 750℃ and hot-extruded into round bars with a diameter of 12mm on an extruder.

[0029] The low coefficient of thermal expansion of the copper material in this embodiment is: an average coefficient of thermal expansion of 6.32*10 at 30~200℃. -6 K -1 .

[0030] The copper powder obtained after reduction and reforming in this embodiment was subjected to EDS elemental distribution analysis. The specific analysis results are as follows: Figures 1 to 6 , Figure 1 Equivalent to Figures 2 to 6 Overlapping overall map; via Figures 2 to 6 As can be seen, the copper powder of the present invention has La, C and B on its surface, and the uniformity is high.

[0031] Figure 7 This is a metallographic image of the copper material of the present invention.

[0032] Example 2 The method is largely the same as in Example 1, except that: the small organic molecule is oleic acid, and its dosage is 0.5g; the boride is boron carbide, and its dosage is 1g.

[0033] Example 3 The method is largely the same as in Example 1, except that the organic small molecules are a mixture of oleic acid and citric acid in a weight ratio of 3:1, with a total amount of 4g; and lanthanum boride is 7g.

[0034] Example 4 The method is largely the same as in Example 1, except that the organic small molecules are a mixture of oleic acid and citric acid in a weight ratio of 6:1, with a total amount of 5g; and lanthanum boride is 10g.

[0035] Comparative Example 1 Generally the same as Example 1, except that: no boride is used; Step 2 is as follows: Step 2: Oleic acid coating: Dissolve 3g of oleic acid and 0.5g of citric acid (i.e., 0.3% oleic acid and 0.05% citric acid) in 1L of anhydrous ethanol. Add this mixture to the copper powder dispersion above and continue stirring for 1.5 hours. Then centrifuge to settle, discard the supernatant, and wash repeatedly with anhydrous ethanol 3 times.

[0036] Comparative Example 2 The general formula is the same as in Example 1, except that small organic molecules are not used. Step 2 is as follows: Step 2: Disperse 5g of lanthanum boride with an average particle size of 100nm (i.e., 0.5% lanthanum boride) in 1L of anhydrous ethanol. Add this mixture to the copper powder dispersion above and continue stirring for 1.5 hours. Then centrifuge to settle, discard the supernatant, and wash repeatedly with anhydrous ethanol 3 times.

[0037] Comparative Example 3 Step 1: Remove oxide film: Add 1 kg of dendritic copper powder to 5 L of high-purity water, disperse by mechanical stirring, add 50 mL of ammonia and 20 mL of hydrazine hydrate, stir at room temperature for 30 minutes to obtain copper powder dispersion.

[0038] Step 2: Oleic acid coating: Disperse 3g of oleic acid and 0.5g of citric acid (i.e., 0.3% oleic acid and 0.05% citric acid) in 1L of anhydrous ethanol. Add this mixture to the copper powder dispersion above and continue stirring for 1.5 hours. Then centrifuge to settle, discard the supernatant, and wash repeatedly with anhydrous ethanol 3 times.

[0039] Step 3: Rotary evaporation drying: Transfer the material to a rotary evaporator, water bath at 65℃, vacuum degree -0.085MPa, and dry until the material is in a loose powder state.

[0040] After drying, add 5g of lanthanum boride with an average particle size of 100nm to the material and stir thoroughly to mix evenly.

[0041] Step 4: Hydrogen reduction and reforming: Place the mixed powder into a tube furnace, introduce a mixture of hydrogen and argon in a ratio of 3:7 (volume ratio), heat to 600°C at 8°C / min, hold for 2 hours, then cool to room temperature with the furnace and remove under a nitrogen atmosphere.

[0042] Step 5: Hot pressing and extrusion: The treated copper powder is placed in a graphite mold and sintered in a vacuum hot press furnace at a temperature of 850℃ and a pressure of 30MPa for 1 hour to obtain copper ingots. The copper ingots are then heated to 750℃ and hot-extruded into round bars with a diameter of 12mm on an extruder.

[0043] Comparative Example 4 Raw material: 1 kg of dendritic electrolytic copper powder (purity ≥ 99.8%, average particle size: 30 μm).

[0044] Step 1: Remove oxide film: Add 1 kg of copper powder to 5 L of high-purity water, disperse by mechanical stirring, add 50 mL of ammonia and 20 mL of hydrazine hydrate, stir at room temperature for 30 minutes to obtain copper powder dispersion.

[0045] Step 2: Polysaccharide Coating: 1.5g of soluble starch (25wt% amylose, gelatinization temperature 65℃) and 5g of lanthanum boride with an average particle size of 100nm (i.e., 1.5% soluble starch, 0.5% lanthanum boride) were dispersed in 1L of anhydrous ethanol. This mixture was added to the copper powder dispersion above, and stirring was continued for 1.5 hours to obtain a mixed solution.

[0046] Step 3: Rotary evaporation drying: Transfer the mixed solution to a rotary evaporator, water bath at 65℃, vacuum degree -0.085MPa, and dry until the material is a loose powder.

[0047] Step 4: Hydrogen reduction and reforming: Place the dry powder into a tube furnace, introduce a mixture of hydrogen and argon in a ratio of 3:7 (volume ratio), heat to 600°C at 8°C / min, hold for 2 hours, then cool to room temperature with the furnace and remove under a nitrogen atmosphere.

[0048] Step 5: Hot pressing and extrusion: The treated copper powder is placed in a graphite mold and sintered in a vacuum hot press furnace at a temperature of 850℃ and a pressure of 30MPa for 1 hour to obtain copper ingots. The copper ingots are then heated to 750℃ and hot-extruded into round bars with a diameter of 12mm on an extruder.

[0049] Comparative Example 5 Raw material: 1 kg of dendritic electrolytic copper powder (purity ≥ 99.8%, average particle size: 30 μm).

[0050] Step 1: Remove oxide film: Add 1 kg of copper powder to 5 L of high-purity water, disperse by mechanical stirring, add 50 mL of ammonia and 20 mL of hydrazine hydrate, stir at room temperature for 30 minutes to obtain copper powder dispersion.

[0051] Step 2: Polysaccharide Coating: Disperse 1.5g of soluble starch (amylose content 25wt%, gelatinization temperature 65℃) in 1L of anhydrous ethanol. Add this mixture to the copper powder dispersion above and continue stirring for 1.5 hours to obtain a mixed solution.

[0052] Step 3: Rotary evaporation drying: Transfer the mixed solution to a rotary evaporator, water bath at 65℃, vacuum degree -0.085MPa, and dry until the material is a loose powder.

[0053] Step 4: Hydrogen reduction and reforming: Place the dry powder into a tube furnace, introduce a mixture of hydrogen and argon in a ratio of 3:7 (volume ratio), heat to 600°C at 8°C / min, hold for 2 hours, then cool to room temperature with the furnace and remove under a nitrogen atmosphere.

[0054] Step 5: Hot pressing and extrusion: The treated copper powder is placed in a graphite mold and sintered in a vacuum hot press furnace at a temperature of 850℃ and a pressure of 30MPa for 1 hour to obtain copper ingots. The copper ingots are then heated to 750℃ and hot-extruded into round bars with a diameter of 12mm on an extruder.

[0055] Performance testing Thermal diffusivity: GB / T 22588-2008; Specific heat capacity: GB / T 22588-2008; Thermal conductivity: GB / T 22588-2008; Sample specifications: specific heat capacity dimensions Φ3mm*2mm; thermal diffusivity dimensions 10mm*10mm*2mm; The test results are shown in Table 1. Table 1 Test Results Example 1 137.797 0.49 8.887 600.055 Example 2 135.436 0.472 8.799 562.48 Example 3 115.94 0.596 8.825 609.81 Example 4 114.115 0.567 8.875 574.24 Comparative Example 1 117.193 0.466 8.913 486.76 Comparative Example 2 108.481 0.453 8.813 433.09 Comparative Example 3 117.279 0.43 8.907 449.180 Comparative Example 4 115.15 0.474 8.839 482.44 Comparative Example 5 114.89 0.471 8.768 474.46

[0056] Results analysis: 1. As can be seen from Examples 1 to 4, coating with oleic acid and / or citric acid, and using borate as an activator and nucleating agent, can effectively improve the thermal conductivity of the product; 2. As can be seen from Comparative Examples 1 and 2, the performance deteriorates significantly when borides or small organic molecules are lacking. The possible reason is that the small organic molecules used in this invention have a certain emulsifying ability. When borides are present, they can encapsulate the borides and form a hydrophobic layer similar to micelles on the surface of copper powder, effectively attaching the borides to the copper powder. During the sintering process, borides can also act as nucleating agents for graphene, reducing defects in graphene and improving thermal conductivity.

[0057] When either of these two is lacking, performance will be significantly reduced.

[0058] 3. As can be seen from the comparison between Example 1 and Comparative Example 3, if borides are added in the later stage through solid blending, they have a negative impact on the thermal conductivity. The main reason is that in Comparative Example 3, the process of coating copper powder with oleic acid first forms a dense organic barrier layer on the surface of the copper powder, which interferes with the subsequent direct contact and reaction between lanthanum boride and copper powder, ultimately hindering the formation of an ideal thermally conductive interface. This oleic acid film barrier physically prevents the direct contact and high-temperature reaction between boron in lanthanum boride and the surface of copper powder. Therefore, boron cannot play its "bridging" role at the key interface, resulting in weak interfacial bonding and high interfacial thermal resistance.

[0059] 4. A comparison of Comparative Examples 4 and 5 with Example 1 shows that the thermal conductivity of polysaccharides and / or borides cannot exceed 500 W / m·K, but it is significantly improved compared to Comparative Example 1. The main reason is that boron doping in Example 1 fundamentally strengthens the interface between graphene and copper, creating a more efficient phonon channel for heat transfer. Comparative Examples 4 and 5, however, are limited by the lack of effective interface modification and the purity of the carbon source, respectively. Although Comparative Example 4 introduces boron, which theoretically improves the interface, the purity, crystallinity, and quality of the carbon material (graphene or amorphous carbon) generated after pyrolysis from its "polysaccharide" are far inferior to those from "oleic acid." The quality difference of the carbon source itself directly affects the quality of the final graphene, and the thermal conductivity of graphene itself is crucial to the overall performance of the composite material. Inferior carbon layers can become new scattering centers, weakening the interface improvement effect brought by boron doping, resulting in a thermal conductivity still lower than that of Example 1.

[0060] However, it is important to note that in the comparisons between Comparative Example 1 and Example 1, and Comparative Example 4 and Comparative Example 5, we found that borides only truly work in the presence of small organic molecules. Under other experimental conditions, borides do not significantly improve thermal conductivity.

Claims

1. A method for preparing a high thermal conductivity graphene-copper composite material, characterized in that, Includes the following steps: Step 1: Remove the surface oxide layer from copper powder with a dendritic structure; Step 2: Disperse the small organic molecules and borides in a good solvent for the small organic molecules, and mix them with the copper powder obtained in Step 1 to separate solid particles; Step 3: Dry the solid particles from Step 2; Step 4: Reduce the dried solid particles; Step 5: Perform hot pressing sintering and molding treatment on the product obtained in Step 4; The weight of the organic small molecule is equivalent to 0.01~0.5% of the weight of the copper powder, and the weight of the boride is equivalent to 0.1~1% of the weight of the copper powder; The small organic molecule is oleic acid or a combination of oleic acid and citric acid; wherein the weight percentage of oleic acid is 75wt%~100wt%.

2. The preparation method according to claim 1, characterized in that, The borides are one or more combinations of boron carbide, molybdenum boride, zirconium boride, nickel boride, lanthanum boride, calcium boride, and yttrium boride.

3. The preparation method according to claim 1, characterized in that, The copper powder has a D50 particle size of 10~35μm; the boride has a D50 particle size of 50~200nm.

4. The preparation method according to claim 1, characterized in that, In step 1, the method for removing the surface oxide layer of copper powder is: reduction by reducing gas or reduction by hydrazine hydrate.

5. The preparation method according to claim 4, characterized in that, Step 1 specifically involves adding copper powder to water, then adding ammonia and hydrazine hydrate for reduction; the product obtained in step 1 is an aqueous solution containing dispersed copper powder.

6. The preparation method according to claim 1, characterized in that, The good solvent in step 2 is anhydrous ethanol; the weight of the good solvent is equivalent to 0.5 to 1.5 times the weight of the copper powder.

7. The preparation method according to claim 1, characterized in that, The mixing time in step 2 is 1-2 hours; the solid particles separated in step 2 are washed with anhydrous ethanol.

8. The preparation method according to claim 1, characterized in that, The drying method in step 3 is one of rotary drying, spray drying, or fluidized bed drying. The reduction method in step 4 is as follows: the reduction operation is carried out in a reducing atmosphere containing hydrogen, and the reduction temperature is 550~650℃.

9. The preparation method according to claim 1, characterized in that, The hot pressing sintering in step 5 is performed at a temperature of 800~1000℃, a pressure of 25~35MPa, and a time of 0.5~1.5h. The molding operation in step 5 is as follows: the copper ingot obtained by hot pressing and sintering is heated to 700~1000℃ and hot extruded to obtain a composite material of the preset specifications.

10. A composite material, characterized in that, It is prepared by the method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Polysaccharide coated-hydrogen pre-sintered dispersed graphene copper composite material and preparation method thereof

    CN121797964A

  • Composite copper powder, preparation method thereof, copper material and application

    CN122231272A

  • Graphene / copper alloy and preparation and application thereof

    CN109112328A

  • In-situ synthesis graphene / copper composite material with oriented bimodal structure and preparation method of in-situ synthesis graphene / copper composite material

    CN117604318A